A comparison of the 31 January–1 February 1953 and 5–6 December 2013 coastal flood events around the UK - Wadey, Matthew P.; Haigh, Ivan. D.; Nicholls, Robert J.; Brown, Jennifer M.; Horsburgh, Kevin; Carroll, Ben; Gallop, Shari L.; Mason, Travis; Bradshaw, Elizabeth (Frontiers in Marine Science, 2015)
A North Sea storm surge during 31 January–1 February 1953 caused Northwest Europe's most severe coastal floods in living memory. This event killed more than 2000 people on the coasts of England, the Netherlands, and Belgium. In the UK, where this study focuses, this event was a pivotal influence for flood risk management. Subsequent progress included a national tide gauge network, a storm surge forecasting and warning service, and major defense upgrades such as the Thames Barrier. Almost 60-years later, on 5–6 December 2013 Storm “Xaver” generated a surge event of similar magnitude. This paper describes a detailed comparison of these two events in the UK in terms of: (1) the meteorological conditions; (2) the observed high sea levels; and (3) the coastal flooding and impacts. The 1953 storm had a more southerly track and generated bigger waves due to the north-northwesterly onshore winds off East Anglia. The 2013 storm had a more west-to-east path from the north Atlantic to Scandinavia. Consequently, the 1953 high waters were more extreme in the southern North Sea. However, the 2013 event coincided with larger astronomical tides, resulting in a larger spatial “footprint”. The extreme sea levels impacted communities on the west, east, and south coasts, with 2800 properties flooded during the 2013 event, compared to 24,000 properties (mainly between the Humber and Thames) in 1953. The 1953 floods remain a benchmark in the UK as an event which included failed defenses, damaged property and infrastructure and loss of life. Measures taken after 1953 greatly reduced the consequences of the 5–6 December 2013 storm. Continued monitoring of extreme sea levels and their consequences is important to inform a realistic perspective on future planning and resilience.